2016
DOI: 10.1016/j.celrep.2016.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Trapped Interactors of PHD3 and FIH Cluster in Distinct Signaling Pathways

Abstract: SummaryAmino acid hydroxylation is a post-translational modification that regulates intra- and inter-molecular protein-protein interactions. The modifications are regulated by a family of 2-oxoglutarate- (2OG) dependent enzymes and, although the biochemistry is well understood, until now only a few substrates have been described for these enzymes. Using quantitative interaction proteomics, we screened for substrates of the proline hydroxylase PHD3 and the asparagine hydroxylase FIH, which regulate the HIF-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 43 publications
4
85
0
1
Order By: Relevance
“…Therefore, mass spectrometry fragmentation data need to be at high resolution and high coverage to confirm the assignment for the modification as previously shown [80]. Many hydroxylation events detected by mass spectrometry may not be mediated by prolyl hydroxylases.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, mass spectrometry fragmentation data need to be at high resolution and high coverage to confirm the assignment for the modification as previously shown [80]. Many hydroxylation events detected by mass spectrometry may not be mediated by prolyl hydroxylases.…”
Section: Introductionmentioning
confidence: 93%
“…[80] were able to identify some novel FIH and PHD substrates. As a proof of principle, they identified some of characterized PHD substrates from this proteomic approach, including CEP192 and FOXO3a [23, 80, 87].…”
Section: Novel Hydroxylation Targets and Their Cellular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study identified FIH as a second, oxygen-dependent hydroxylase that targets HIF (77,78). Subsequent studies demonstrated that while HIF is clearly the major pathway regulated by hydroxylation, signaling components of other pathways such as NF-κB are also subject to enzymatic hydroxylation, although the functional consequences of hydroxylation for non-HIF targets remains an area under investigation (62)(63)(64)79).…”
Section: Regulation Of Immune Cell Function By Phdsmentioning
confidence: 99%
“…Upon reconstitution, the EGFP has been observed to evidence a restored fluorescence upon protein-protein interactions in yeast, allowing for the characterization of its interactor. With standard Y2H assays, detection of an interaction requires that two proteins localize to the nucleus [32,33]. In 2007, a yeast-based genetic technology for the in vivo detection of membrane protein interactors was developed and is referred to as the split-ubiquitin membrane yeast two-hybrid system.…”
Section: Y2h Pairwise Screeningmentioning
confidence: 99%